Metformin Affects Gut Microbiota Composition and Diversity Associated with Amelioration of Dextran Sulfate Sodium-Induced Colitis in Mice - Liu, Zhiyi; Liao, Wangdi; Zhang, Zihan; Sun, Ruipu; Luo, Yunfei; Chen, Qiongfeng; Li, Xin; Lu, Ruiling; Ying, Ying (Frontiers in Pharmacology, 2021)
Background: Inflammatory bowel disease (IBD) is an increasingly common and globally emergent immune-mediated disorder. The etiology of IBD is complex, involving multiple factors such as immune dysregulation, environmental factors, genetic mutations, and microbiota dysbiosis, exacerbated by a lack of effective clinical therapies. Recently, studies hypothesized that dysbiosis of intestinal flora might participate in the onset of IBD. Metformin is widely used to treat type 2 diabetes and has shown beneficial effects in mouse models of IBD, although its underlying mechanisms remain poorly understood. Accumulating studies found that metformin shows beneficial effects for diabetes by affecting microbiota composition. This study explores possible therapeutic mechanisms of metformin on IBD through effects on intestinal microecology. Methods: Inflammation was induced using 3% Dextran Sulfate Sodium (DSS) solution to generate mice models of IBD. Metformin treatments were assayed by measuring body weights and colon lengths of mice and H&E staining to observe histological effects on colon tissue structures. Changes in bacterial community composition and diversity-related to IBD and metformin treatment were assessed by high-throughput metagenomic sequencing analysis. Results: Metformin administration significantly ameliorated body weight loss, reduced colon length, and contributed to preserving the integrity of colon histological structures. The gut microbiota profiles revealed that the biodiversity of intestinal flora lost during inflammation was restored under metformin treatment. Metformin administration was also associated with decreased pathogenic Escherichia shigella and increased abundance of Lactobacillus and Akkermansia. Conclusion: Metformin appears to induce anti-inflammatory effects, thus ameliorating colitis symptoms, concurrent with enrichment for beneficial taxa and restored microbial diversity, suggesting a viable strategy against IBD.